2009
DOI: 10.4319/lo.2009.54.3.0746
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of calcium in Daphnia magna reared in different calcium environments

Abstract: The specific content, dissolved uptake rate, dietary assimilation efficiency (AE), and efflux rate constant (k e ) of calcium (Ca) were quantified in juvenile (4-d) and adult (10-d) Daphnia magna cultured in low (0.5 mg L 21 )-and high (50 mg L 21 )-Ca environments using a radiotracer technique. Daphnids raised in the high-Ca environment had higher Ca contents than did those raised in the low-Ca environment, and juvenile daphnids had higher Ca contents than adults. Uptake from solution was the dominant source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 39 publications
3
48
2
Order By: Relevance
“…The release of P contained in the molting fluid was another possible explanation (Peters & Rigler 1973). A higher release rate during molting was also observed for Ca (Tan & Wang 2009), again suggesting the association of P and Ca in the molting process.To conclude, Daphnia magna living in a higher Ca environment had a lower specific P content, and there was a negative relationship between P and Ca contents. Therefore, Ca concentration should be considered when comparing the P content of daphnids collected from different localities.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The release of P contained in the molting fluid was another possible explanation (Peters & Rigler 1973). A higher release rate during molting was also observed for Ca (Tan & Wang 2009), again suggesting the association of P and Ca in the molting process.To conclude, Daphnia magna living in a higher Ca environment had a lower specific P content, and there was a negative relationship between P and Ca contents. Therefore, Ca concentration should be considered when comparing the P content of daphnids collected from different localities.…”
mentioning
confidence: 93%
“…The actual Ca concentrations were measured at the beginning and end of all experiments, and the average values matched well with the nominal concentrations (see Table 1). Because water is the principal source of Ca for Daphnia magna (Tan & Wang 2009), algae cultured in 0.5 mg Ca l -1 WC medium were used for all treatments in all experiments in order to avoid any difference in food.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether AgNPs have similar effects on the Na flux and the underlying mechanism is still not known. In addition, daphnids require a large amount of Ca during their life cycle [19]. Calcium regulation may play an important role not only in molting but also in other capacities such as nerve function.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium regulation may play an important role not only in molting but also in other capacities such as nerve function. It was found that nanoparticles could affect the Ca content in cell lines and cause an abrupt increase of both extracelluar and intracellular Ca influx [19]. Whether AgNPs can affect the Ca homeostasis and regulation in daphnids is still unknown.…”
Section: Introductionmentioning
confidence: 99%